Promoting sustainability through water hydraulic technology -the effect of water hydraulic in industrial scissor lift - Yusof, Ahmad Anas; Mat, Shafizal; Din, Abdul Talib (Trans Tech Publication, Switzerland, 2013)
Sustainability concern has brought the idea of exploring the possibility of using water as the hydraulic medium to transfer energy. The abundant resource of water, and its characteristic involving hygiene, safety and low maintenance cost provides a fascinating perspective of choosing water over hydraulic oil, due to concerns over oil disposal, contamination, costly maintenance and flammability. However, in contrast, its low boiling temperature, low viscosity, and simple molecular structure could pose danger to the operation of the hydraulic system. In order to identify these limitations, an experimental study is carried out to explore the effect of water hydraulic system. A test rig of scissor lift is fabricated and put into test by replacing the hydraulic oil with reverse osmosis water. It is found that the water hydraulic scissor lift managed to lift up to 400 kg of load, with workable water temperature of 41.4oC.